Context awareness: Challenges and opportunities in modern smartphone use - Paspallis, Nearchos; Panis, Gabriel (Electronic Communications of the EASST, 2011)
Commonly, improvement to smart-phone technology focuses at advancing the connectivity of human users. This results to better and richer information access but, undeniably, it also increases the accessibility of the users themselves, something that could arguably have negative side-effects. This position paper discusses the potential of context awareness in modern smart-phones by presenting the challenges and opportunities in modern smartphone use. In particular, we examine the implications of the advanced network capabilities—and accompanying services—of modern smart-phones and list what we argue to be their main drawbacks. We then present our position which summarizes what we expect the role of context-awareness to be in modern smart-phone applications.